2023
DOI: 10.1108/ijdrbe-02-2023-0025
|View full text |Cite
|
Sign up to set email alerts
|

Performance indicators for public evaluation of environmental management plan implementation in highway construction projects

Nurol Huda Dahalan,
Rahimi A. Rahman,
Siti Hafizan Hassan
et al.

Abstract: Purpose Evaluating the implementation of environmental management plans (EMPs) in highway construction projects is essential to avoid climate change. Public evaluations can help ensure that the EMP is implemented correctly and efficiently. To allow public evaluation of EMP implementations, this study aims to investigate performance indicators (PIs) for assessing EMP implementation in highway construction projects. To that end, the study objectives are to compare the critical PIs between environment auditors (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…A comparison of this study's results with prior findings offers a nuanced understanding of the PIs for assessing EMP implementation. Specifically, this study's outputs were compared with PIs identified in the context of road construction [16] and highway construction projects [17], revealing both commonalities and disparities. Table 8 captures the essence of this comparative analysis, indicating that out of the 18 critical PIs identified in this study, 6 were not deemed critical in prior works.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…A comparison of this study's results with prior findings offers a nuanced understanding of the PIs for assessing EMP implementation. Specifically, this study's outputs were compared with PIs identified in the context of road construction [16] and highway construction projects [17], revealing both commonalities and disparities. Table 8 captures the essence of this comparative analysis, indicating that out of the 18 critical PIs identified in this study, 6 were not deemed critical in prior works.…”
Section: Comparison With Prior Workmentioning
confidence: 99%